1973
DOI: 10.1093/jaoac/56.4.922
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of the AOAC Method of Analysis for Nitrite in Meat

Abstract: Results of studies on the effects of 5 alternative procedures of sample preparation are presented. The standard deviations for the methods were 0.00505, 0.00142, 0.00307, 0.00265, and 0.00243, with the AOAC method giving the highest values for nitrite. The effects of some variables on the determination of the nitrite content of meat by the official method were also studied. These variables include the addition of mercuric chloride, duration of heating, rate of color reaction, and reagent preparation. The nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The single-ion activity was calculated by the following equations22 logy, = IZ+/Z-llogy, logy-= Iz-/z+(logyk Macerated Chinese cabbage kept for 24 h at 25°C was treated according to the literature method. 23 The sample was analysed by both the electrode method and by spectrophotometry after being diluted 20-fold. The measurements of both the potentiometric selectivity coefficients and the concentration of NO2in Chinese cabbage were carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The single-ion activity was calculated by the following equations22 logy, = IZ+/Z-llogy, logy-= Iz-/z+(logyk Macerated Chinese cabbage kept for 24 h at 25°C was treated according to the literature method. 23 The sample was analysed by both the electrode method and by spectrophotometry after being diluted 20-fold. The measurements of both the potentiometric selectivity coefficients and the concentration of NO2in Chinese cabbage were carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…With fresh solutions, the cumulative coefficient of variation was ±2.5%. Standard dilution curves had coefficients of variation (at 10 µ N02") about 1%, and in a study of the AOAC method of nitrite analysis (9) we obtained an average coefficient of variation of 1.5%. In contrast, collaborative studies have shown inter-laboratory coefficients of variation of 9% (22) and 11% (13) for residual nitrite in cured meat products.…”
Section: Effect Of Varying the [Ns] And [Cr]mentioning
confidence: 79%
“…Ilosvay (6) first recommended the use of acetic acid which results in reaction solution pH values in the range of maximal conversion, pH 2.5-3.0 (7), for the sulfanilic acid/1naphthylamine reactions, but whether this is a universal range is not well established. The NS must be in at least 100-fold molar excess over nitrite for maximal pigment production (8,9). It has long been known that with a large excess of nitrite only yellow colors are produced (10), but the effect of large excesses of reagents has not been studied, nor have the optimal reagent concentrations been established.…”
mentioning
confidence: 99%
“…Therefore, if the two reagents are added together this competing reaction can lead to the destruction of some nitrite and loss of color. For this reason, both the AOAC and the European Economic Community (EEC) methods call for the separate 24 8 N. P. SEN AND M. McPHERSON addition of the two color reagents (Fiddler 1977;Nicholas and Fox 1973). Sulfanilamide is added first, and after 5 min (when the diazotization reaction is complete) N-( l-naphthy1)ethylenediamine is added to form the pink azo dye.…”
Section: Introductionmentioning
confidence: 99%